Penguatan Nilai Karakter Bagi Siswa Sekolah Dasar Di Tengah Pandemik COVID -19 - Jamilah, Jamilah; Sukitman, Tri (JIKAP PGSD: Jurnal Ilmiah Ilmu Kependidikan, 2021)
The COVID-19 pandemic has changed various aspects of human life today, especially in the field of education. With the outbreak of the COVID-19 virus or known as the coronavirus in Indonesia, the government has forced the government to issue a policy to divert learning that has been carried out directly (teachers and students meeting each other) at school to online learning. One of the activities that occurred indirectly during the COVID-19 pandemic was planting and strengthening children's character education. This research is a descriptive type of research used to describe how to strengthen character education for elementary school students during the COVID 19 pandemic. The research subjects consisted of 5 elementary school students and 2 educators. The data were collected using semi-structured interview data via video conference, and documentation. This study was analyzed using qualitative descriptive. The results of this study show that strengthening children's character education during the COVID-19 pandemic through habituation, independence, religion, and integrity.